Review of Nineteenth- and Twentieth-Century Readings of the Medieval Orient: Other Encounters by Liliana Sikorska - Buchholtz, Mirosława (Studia Anglica Posnaniensia, 2023)
Review of Nineteenth- and Twentieth-Century Readings of the Medieval Orient: Other Encounters by Liliana Sikorska.